ORIENTATION OF THE 700-M MIZUHO CORE AND ITS STRAIN HISTORY - フジタ, シュウジ; ナカワ, マサヨシ; マエ, シンジ; FUJITA, Shuji; NAKAWO, Masayoshi; MAE, Shinji (National Institute of Polar Research, 1987)
P(論文) Structual analyses of the core revealed that the ice fabric pattern as well as the shape of individual ice grains and air bubbles exhibited strong anisotropies. They were correlated with the stress conditions of the ice sheet around the station. This became possible by an estimation of the geographical orientation of the core through measurements of the natural remanent magnetization formed accidentally. It was found that ice grains and air bubbles were elongated in the direction of flow, which was identical with the direction of the tensile strain. Also, c-axes of the ice grains tended to orient perpendicular to the tensile axis, forming a vertical great girdle pattern, which is considered to have resulted from by the gradual rotation of the ice grains toward a plane normal to the tensile axis. The rotation of the grains was calculated with respect to the total strain, simulating a formation of the great girdle fabric pattern. By comparing the simulated fabric pattern with the measured pattern of the Mizuho core, the accumulated strain in the core ice was estimated at various depths. The total strain the core ice has experienced increased almost linearly with depth at a rate of about 20% per 100m. departmental bulletin paper